Andreas Papandreou’s Exile Politics: The First Phase (1968-1970) - Draenos, Stan (The Historical Review/La Revue Historique, 2014)
Andreas Papandreou’s exile politics, following his December 1967 release from Averoff Prison, have stereotypically been seen as simply adopting the neo-Marxist ideologies associated with the Third World national liberation movements of the era. In narrating the initial evolution of his views on the “Greek Question” in exile, this study attempts to surface the underlying dynamics responsible for radicalizing his politics in that direction. Those dynamics reflect, on the one hand, the relentless will-to-action informing Papandreou’s political persona and, on the other, the political upheavals, headlined by the protest movement against the US war in Vietnam, in which his politics were enmeshed.